2020
DOI: 10.3390/plants9040492
|View full text |Cite
|
Sign up to set email alerts
|

The Spread and Transmission of Sweet Potato Virus Disease (SPVD) and Its Effect on the Gene Expression Profile in Sweet Potato

Abstract: Sweet potato virus disease (SPVD) is the most devastating viral disease in sweet potato (Ipomoea batatas (L.) Lam.), causing substantial yield losses worldwide. We conducted a systemic investigation on the spread, transmission, and pathogenesis of SPVD. Field experiments conducted over two years on ten sweet potato varieties showed that SPVD symptoms first occurred in newly developed top leaves, and spread from adjacent to distant plants in the field. The SPVD incidence was mainly (but not only) determined by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 56 publications
0
6
0
1
Order By: Relevance
“…Natural infection and human friction are commonly used in virus inoculation or detection. Studies have shown that grafting can transmit SPVD more effectively than friction in sweet potatoes [ 37 ], possibly because SPCSV is restricted by phloem, and grafting would facilitate SPCSV transmission into the phloem. SPCSV could then enhance the multiplication of SPFMV and increase the titer of SPFMV in non-phloem tissues, causing severe SPVD symptoms [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Natural infection and human friction are commonly used in virus inoculation or detection. Studies have shown that grafting can transmit SPVD more effectively than friction in sweet potatoes [ 37 ], possibly because SPCSV is restricted by phloem, and grafting would facilitate SPCSV transmission into the phloem. SPCSV could then enhance the multiplication of SPFMV and increase the titer of SPFMV in non-phloem tissues, causing severe SPVD symptoms [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Los posibles efectos generados en las plantas enfermas evaluadas durante el período de fase 2 y principio de la fase final de crecimiento, se deberían a un retraso en los procesos de tuberización, además de una reducción de la actividad fotosintética. Según Zhang et al (2020), ambos procesos se estimulan mutuamente y limitan la máxima eficiencia de la planta, afectando de manera indirecta al rendimiento. Los resultados obtenidos indicaron (datos no mostrados) que las lecturas de SPAD en hojas de plantas sanas, aumentaron de manera gradual durante el período de crecimiento desde principios de enero hasta mediados de febrero, seguido de una reducción a mediados de marzo, al final del período vegetativo.…”
Section: Contenido De Clorofilaunclassified
“…Taken together, properties of the virus, its response to deployment of resistance genes, and vector relationships, and how these come together in an epidemiological framework, offer the best clues to disease management but it remains unclear how widely these can be applied across different geographical locations, potato cultivars, and strains of the virus. Epidemics of sweet potato virus disease (SPVD, caused by sweet potato feathery mottle virus and sweet potato chlorotic stunt virus) were monitored over time and with leaf profile for 10 sweet potato varieties covering a range of resistance characteristics [ 98 ]. The data provided detailed information on the development of SPVD and the molecular responses that were occurring in the field based on transcriptomics.…”
Section: Epidemiology and Disease Controlmentioning
confidence: 99%